The classification of the Galilei-invariant systems of nonlinear reaction-diffusion equations - Barannyk, T.A. (Reports of the National Academy of Sciences of Ukraine, 2015)
The full description of the Galilei-invariant systems of nonlinear reaction-diffusion equations is presented in the case where the roots of the characteristic equation of the diffusion matrix are real numbers.